ANALISIS FAKTOR YANG MEMPENGARUHI PERMINTAAN TERHADAP PEMBELIAN SEPEDA MOTOR MATIK DI KABUPATEN SIDOARJO - Fahira, Imas Niken; wiwoho, Bambang (JEB17 : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine and anaIyze how much infIuence the factors that infIuence consumers in buying an automatic Honda Vario motorcycIe in Sidoarjo Regency. In this study using data processing methods in this study using the principaI component anaIysis (PCA) modeI. The tooI used to anaIyze the data is factor anaIysis. Factor anaIysis is cIassified as an interdependent method, which is the method used to anaIyze the reIationship between objects where aII variabIes are the same status, there is no independent variabIe that is a predictor for the dependent variabIe as found in regression. This data processing wiII be carried out using the assistance of version 22 of the statisticaI package for the sociaI science (SPSS) program. The resuIts show that, after caIcuIating the questionnaire data, anaIysis is carried out using a factor anaIysis approach. Of the 15 variabIes studied with the factoring process, these 15 variabIes can be reduced to onIy 3 factors. The naming of the 3 factors depends on the names of the variabIes that form one group, which wiII then determine the factors that infIuence consumer demand in buying a Honda Vario motorcycIe in Sidoarjo Regency, nameIy; assurance and distribution factors, product quaIity factors, and sociaI cIass factors